Electronic cigarette use and risk perception in a Stop Smoking Service in England. (August 2015) - Sherratt, Frances C.; Marcus, Michael W.; Robinson, Jude; Newson, Lisa; Field, John K.
Abstract Introduction: Electronic cigarette (e-cigarette) use rose substantially within the UK in recent years but currently, Stop Smoking Services in England do not prescribe them due to a lack of regulation. Previous research has examined e-cigarette use and attitudes within English Stop Smoking Services using samples of practitioners and managers; the current study recruited a sample of service users. Methods: Participants (N = 319) aged 18–60 years old were recruited from Roy Castle FagEnds, Liverpool, England (Stop Smoking Service). A cross-sectional questionnaire was completed, which recorded demographic variables, e-cigarette use alongside risk perception, and lastly, smoking behaviour i.e. smoking duration, cigarettes per day, and nicotine dependence. Results: Most participants were female (57.1%), current smokers (53.0%), and current or former e-cigarette users (51.7%). Participants who perceived e-cigarettes as less harmful than smoked tobacco were more likely to have smoked fewer cigarettes per day (p = 0.008). Furthermore, those who felt uncertain whether e-cigarettes were safer than smoked tobacco, were less likely to have tried them (p < 0.001). Conclusion: This study suggests that e-cigarette use is becoming common among users of Stop Smoking Services (despite e-cigarettes being unavailable from such services) and that e-cigarette risk perception is related to e-cigarette status. The results highlight the importance of providing smokers intending to quit smoking with current and accurate e-cigarette information. Findings may inform future Stop Smoking Services provision and the results demonstrate that further research is warranted.